Nanostructures of carbon in nuclear graphite - Wen, K; Marrow, J; Marsden, B (2008)
A variety of nanostructures of carbon in nuclear graphite were revealed by transmission electron microscopy (TEM) and high resolution TEM. Theses nanostructures include nanosized graphite particles, quinoline insoluble particles, a chaotic structure and a non-graphitizable structure of carbon. The basic structure of these nanostructures was observed to be nanosized packets of graphitic sheets or nanosized graphene. © 2008 IOP Publishing Ltd.